2005
DOI: 10.1016/j.ssc.2005.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Na0.3RhO2·0.6H2O—a semiconductor with a weak ferromagnetic component

Abstract: We have prepared the oxyhydrate Na 0.3 RhO 2 ⋅0.6H 2 O by extracting Na + cations from NaRhO 2 and intercalating water molecules using an aqueous solution of Na 2 S 2 O 8 . Rietveld refinement, thermogravimetric analysis (TGA), and energy-dispersive x-ray analysis (EDX) reveal that a non-stoichiometric Na 0.3 (H 2 O) 0.6 network separates layers of edge-sharing RhO 6 octahedra containing Rh 3+ (4d 6 , S=0) and Rh 4+ (4d 5 , S=1/2). The resistivities of NaRhO 2 and Na 0.3 RhO 2 ·0.6H 2 O (T < 300) reveal insula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…This exhibits superconductivity at approximately 4.6 K. Li x CoO 2 Á yH 2 O and K x CoO 2 Á yH 2 O, which may also include H 3 O ions, were reported soon after the discovery of the superconductor with Na [23][24][25] and do not exhibit superconductivity. Many oxides with different transition metal ions but similar crystal structures to BLH or MLH exist [26][27][28][29][30], which also do not exhibit superconductivity. On the other hand, superconductivity is induced by similar hydration in niobium and tantalum sulfates [31,32], although the NbS 2 /TaS 2 layer is largely different from the CoO 2 layer in BLH or MLH; the niobium or tantalum ions are coordinated in trigonal prisms of sulfur ions [33].…”
Section: Chemical Compositions and Crystal Structuresmentioning
confidence: 99%
“…This exhibits superconductivity at approximately 4.6 K. Li x CoO 2 Á yH 2 O and K x CoO 2 Á yH 2 O, which may also include H 3 O ions, were reported soon after the discovery of the superconductor with Na [23][24][25] and do not exhibit superconductivity. Many oxides with different transition metal ions but similar crystal structures to BLH or MLH exist [26][27][28][29][30], which also do not exhibit superconductivity. On the other hand, superconductivity is induced by similar hydration in niobium and tantalum sulfates [31,32], although the NbS 2 /TaS 2 layer is largely different from the CoO 2 layer in BLH or MLH; the niobium or tantalum ions are coordinated in trigonal prisms of sulfur ions [33].…”
Section: Chemical Compositions and Crystal Structuresmentioning
confidence: 99%
“…The material is a semiconductor with transport and optical band gaps of about 0.16 eV, effective magnetic moment of about 1.5 µB per formula unit, a Curie Weiss theta of about -2.8 K, no magnetic ordering observed down to 0.35 K, and an anomalous heat capacity is seen at low temperatures. The magnetic moment, which is low but present, makes this a rare but not unique example of a magnetic rhodium oxide 4,16,26,27 . The heat capacity at low temperatures (~0.35 K) follows a power law with an exponent of 0.57, much smaller than the expected value of 3, and shows an upturn under zero applied magnetic field that is suppressed by applied fields larger than 2 Tesla.…”
Section: Introductionmentioning
confidence: 96%
“…After the discovery of superconductivity in Na0.35CoO2.1.6H2O 1,2 , the search for structurally and chemically related superconductors became of significant interest [3][4][5] . A metalinsulator transition was found in NaxRhO2 at x = 0.67, for example, but superconductivity was not observed 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Na x RhO 2 it has been shown that the water intercalation and the elongated unit cell result in a decrease of the resistivity18. Accordingly, in Ref.…”
mentioning
confidence: 96%